Glomerular Disease in Patients with Infectious Processes Developing Antineutrophil Cytoplasmic Antibodies. (19th February 2013) - Konstantinov, Konstantin N.; Emil, Suzanne N.; Barry, Marc; Kellie, Susan; Tzamaloukas, Antonios H.
Abstract : To identify differences in treatment and outcome of various types of glomerulonephritis developing in the course of infections triggering antineutrophil cytoplasmic antibody (ANCA) formation, we analyzed published reports of 50 patients. Immunosuppressives were added to antibiotics in 22 of 23 patients with pauci-immune glomerulonephritis. Improvement was noted in 85% of 20 patients with information on outcomes. Death rate was 13%. Corticosteroids were added to antibiotics in about 50% of 19 patients with postinfectious glomerulonephritis. Improvement rate was 74%, and death rate was 26%. Two patients with mixed histological features were analyzed under both pauci-immune and post-infectious glomerulonephritis categories. In 9 patients with other renal histology, treatment consisted of antibiotics alone (7 patients), antibiotics plus immunosuppressives (1 patient), or immunosuppressives alone (1 patient). Improvement rate was 67%, permanent renal failure rate was 22%, and death rate was 11%. One patient with antiglomerular basement disease glomerulonephritis required maintenance hemodialysis. Glomerulonephritis developing in patients who became ANCA-positive during the course of an infection is associated with significant mortality. The histological type of the glomerulonephritis guides the choice of treatment. Pauci-immune glomerulonephritis is usually treated with addition of immunosuppressives to antibiotics.